Praktik Ekonomi Islam pada Komunitas Keagamaan di Sulawesi Selatan - Mustaqim Pabbajah (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
This article aims to explain the implementation of the Islamic economic system in the process and practice of community empowerment by selecting the An-Nadzir religious community in South Sulawesi as the basis for its analysis. In this case An-Nadzir developed as an independent religious community with the application of Islamic economics in social-economic life. This research is done by qualitative data collection, then presented in descriptive analysis. In the era of the ASEAN economic community and the current global economic competition, various forms of strategy and implementation of the economic system need to be done. One is the implementation of Islamic economics with the empowerment of society as a practical offer. This is endeavourmust be implemented through the empowerement the middle to lower community in order to create a strong, creative, and more independent society. The social-economic empowerment of religious communities is one of the bids as an alternative to implementing the Islamic economic system.